Performance Analysis and Optimization of Built-In Permanent Magnet and Salient-Pole Electromagnetic Hybrid Excitation Generators for Vehicles - Huihui Geng; Xue-Yi Zhang; Yanhong Gao; Shilong Yan; Yufeng Zhang; Yutong Han; Lei Wang; Sizhan Hua (Journal of Engineering)
To solve the problems of the low power density of pure electric excitation generator and nonadjustable magnetic field of pure permanent magnet (PM) generator, a salient-pole hybrid excitation generator (HEG) was proposed in this paper. The designed generator realized coexcitation of two magnetic fields by changing the shape of the pole shoes and embedding the combined-pole PM steels. Compared with other HEGs, it had the advantages of high power density, less excitation loss, and small volume. The paper deduced the analytical expressions of the main magnetic field and armature reaction magnetic field of the HEG and analyzed the armature reaction magnetic circuit, the main influencing parameters, and the influence law of each parameter on the generator output performance to complete the parameter matching of the whole machine. The prototype was trial manufactured and tested with the optimized parameters. The results show that the designed HEG has a low voltage regulation rate, good no-load characteristics, and regulation characteristics. It can ensure the regulated output voltage under rated load conditions and meet the application requirement.